Minutes of 10th technical and progress monitoring (TPM) meeting of BRACU new campus (session l) - Brac University (Brac University, 2023)
Minutes of the 10th Technical and Progress Monitoring (TPM) meeting (session l) of BRACU new campus, held on 19th January, 2018.